2016
DOI: 10.3892/or.2016.5060
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch repair gene mutation spectrum in the Swedish Lynch syndrome population

Abstract: Abstract. Lynch syndrome caused by constitutional mismatch-repair defects is one of the most common hereditary cancer syndromes with a high risk for colorectal, endometrial, ovarian and urothelial cancer. Lynch syndrome is caused by mutations in the mismatch repair (MMR) genes i.e., MLH1, MSH2, MSH6 and PMS2. After 20 years of genetic counseling and genetic testing for Lynch syndrome, we have compiled the mutation spectrum in Sweden with the aim to provide a population-based perspective on the contribution fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 31 publications
5
30
0
Order By: Relevance
“…Slightly higher values (53–62%) have been obtained in other Scandinavian cohorts (Lagerstedt Robinson et al 2007; Sjursen et al 2010). The distribution of mutations in the MMR genes in our cohort is largely similar to that recently reported in a Swedish national LS cohort, i.e., mutations in MLH1 and MSH2 predominate (Lagerstedt-Robinson et al 2016). …”
Section: Discussionsupporting
confidence: 88%
“…Slightly higher values (53–62%) have been obtained in other Scandinavian cohorts (Lagerstedt Robinson et al 2007; Sjursen et al 2010). The distribution of mutations in the MMR genes in our cohort is largely similar to that recently reported in a Swedish national LS cohort, i.e., mutations in MLH1 and MSH2 predominate (Lagerstedt-Robinson et al 2016). …”
Section: Discussionsupporting
confidence: 88%
“…Additional findings on ES included a heterozygous, de novo, and terminal deletion of MSH2 . This deletion involves exons 11–16 ([NM_000251.2] arr[GRCh37] 2p21(47,695,322–47,710,345) × 1) of the gene and has been previously reported as pathogenic of hereditary nonpolyposis colorectal cancer (HNPCC) (Lynch syndrome) in several families (Lagerstedt‐Robinson et al, ; Martínez‐Bouzas et al, ; McPhillips, Meldrum, Creegan, Edkins, & Scott, ; Romero et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, to put the scope of our study in perspective, a recent study reported that 369 Lynch syndrome families were identified in Sweden but no information was given on how many persons were tested for mutations 15 . The authors estimated that no more than one-quarter of the mutation carriers had been identified in Sweden which may imply that some 1500 Lynch syndrome families would exist.…”
Section: Discussionmentioning
confidence: 99%